2003
DOI: 10.1016/s0736-0266(02)00141-9
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1β induces COX2, MMP‐1, ‐3 and ‐13, ADAMTS‐4, IL‐1β and IL‐6 in human tendon cells

Abstract: Overuse injuries and trauma in tendon often involve acute or chronic pain and eventual matrix destruction. Anti-inflammatory drugs have been used as a treatment, however, the cellular and molecular mechanisms of the destructive processes in tendon are not clearly understood. It is thought that an inflammatory event may be involved as an initiating factor. Mediators of the inflammatory response include cytokines released from macrophages and monocytes. Interleukin-1 beta (IL-1 p) is a candidate proinflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
293
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(317 citation statements)
references
References 43 publications
24
293
0
Order By: Relevance
“…Our results are consistent with the previous observation that exogenous PGE 2 up-regulates MMPs in gingival fibroblasts (Sakaki et al, 2004). Other studies have reported that PGE 2 mediates IL-1β-induced MMP-1 up-regulation in tendon and gingival fibroblasts (Domeij et al, 2002;Tsuzaki et al, 2003). It is noted that tendon consists predominantly of collagen type I with a triple helical structure that resists general proteolytic degradation but is susceptible to MMPs.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with the previous observation that exogenous PGE 2 up-regulates MMPs in gingival fibroblasts (Sakaki et al, 2004). Other studies have reported that PGE 2 mediates IL-1β-induced MMP-1 up-regulation in tendon and gingival fibroblasts (Domeij et al, 2002;Tsuzaki et al, 2003). It is noted that tendon consists predominantly of collagen type I with a triple helical structure that resists general proteolytic degradation but is susceptible to MMPs.…”
Section: Discussionsupporting
confidence: 93%
“…IL-1β has previously been shown to increase ADAMTS expression in other systems such as a murine colon carcinoma cell line [17] and in human tendon cells [42]. The increase in cytokine expression following stroke has previously been documented by 15 others [4], [20], [27], [36].…”
Section: Discussionmentioning
confidence: 92%
“…Unexpectedly, however, no detectable aggrecanase-1 mRNA expression was found in chondrocytes cultured with T-2 toxin in vitro. Previous studies have shown that aggrecanase-1 usually is an up-regulated expression in the cartilage induced by IL-1 (Liacini et al, 2005;Tsuzaki et al, 2003;Pratta et al, 2003), whereas aggrecanse-2 mRNA is expressed constitutively in cartilage, and the aggrecanase activity of aggrecanase-2 was at least 1 000-fold greater than that of aggrecanase-1 (Gendron et al, 2007). Therefore, aggrecanase-2 is a major aggrecanase in cartilage metabolism and pathology.…”
Section: Discussionmentioning
confidence: 96%